2013
DOI: 10.3989/cyv.182013
|View full text |Cite
|
Sign up to set email alerts
|

Propiedades mecánicas del telururo de bismuto (Bi<sub>2</sub>Te<sub>3</sub>) procesado mediante torsión bajo alta presión (HPT)

Abstract: INTRODUCCIÓNEl rendimiento de los materiales termoeléctricos a una temperatura dada, T, suele definirse mediante la figura de mérito (Z), donde Z es función del coeficiente de Seebeck (α), la conductividad eléctrica (σ) y la conductividad térmica (κ):De acuerdo con la ecuación [1], para incrementar la figura de mérito es necesario incrementar el coeficiente de Seebeck y la conductividad eléctrica y disminuir la conductividad térmica. Sin embargo, estas tres magnitudes dependen de la concentración de portadores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Nowadays, the practical applications of TE devices are limited to materials which display high ZT values at relatively low temperatures [4][5][6]. As a consequence, the niche applications of these materials are strongly limited by temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the practical applications of TE devices are limited to materials which display high ZT values at relatively low temperatures [4][5][6]. As a consequence, the niche applications of these materials are strongly limited by temperature.…”
Section: Introductionmentioning
confidence: 99%
“…High-pressure torsion (HPT) deformation is considered one of the successful approaches to induce high dislocation densities to TE materials, in which high strains are attainable with relatively minimal cracking, as opposed by simple tensile or compression deformation [148][149][150][151][152][153][154][155][156][157][158][159][160][161]. In one of the successful applications of HPT, Rogl et al showed that although the high temperature HPT increased significantly the electrical resistivity of impure DD 0.40-Fe 2.8 Co 1.2 Sb 12 (DD stands for didymium, a binary Nd-4.8 wt% Pr alloy), the enhancement in the Seebeck coefficient (120-210 mV/K @ 800 K) and the drop in the thermal conductivity (35-23 mW/cm•K @ 800 K) led to a zT enhancement from 0.5 of the undeformed sample to 1.38 after deformation [153].…”
Section: Targeting High Zt Through Intentional Plastic Deformationmentioning
confidence: 99%
“…In the field of severe plastic deformation (SPD) (Azushima et al, 2008;Brown et al, 2009;Edalati et al, 2022;Mansoor and Dasharath, 2020;Valiev et al, 2000), researchers impart extreme strain into materials-typically metals-to attain enhanced structural and functional properties through novel microstructures (Estrin and Vinogradov, 2013). The diverse SPD processes and materials include equal-channel angular extrusion (Furukawa et al, 2002), high-pressure torsion of bismuth telluride (Santamarı´a et al, 2013), cyclic extrusion and compression of aluminum (Richert et al, 1999), accumulative roll bonding of copper with niobium (Nizolek et al, 2016), friction welding of superalloys (Li et al, 2012), and shear-assisted processing and extrusion (ShAPE) of magnesium and aluminum (Whalen et al, 2019a(Whalen et al, , 2019b.…”
Section: Introductionmentioning
confidence: 99%